Pengaruh Pemahaman Literasi Keuangan dan Gaya Hidup terhadap Perilaku Konsumtif Santri Putri Al-Hidayah Ketegan Tanggulangin Sidoarjo - Adelia Anggraeni (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2025)
This research aims to determine the influence of financial literacy and lifestyle on the consumptive behavior of al-Hidayah female students. This research uses quantitative methods with data and information collection techniques obtained directly from respondents. The sample in this study consisted of 86 respondents from 623 students using the Slovin formula. The data analysis technique uses a questionnaire with SPSS version 25 tools. The results of this research show that the influence of financial literacy has a significant effect on consumer behavior. Simultaneously, financial literacy and lifestyle have a significant effect on consumer behavior with a coefficient of determination of 48.2%.